Integrating informal waste pickers and recyclers into the Extended Producer Responsibility (EPR) system to achieve plastic circularity in Indonesia - Yolanda, Kristina; Visvanathan, C.; Tatchai Pussayanavin; Guerrero Cruz, Simon; Government of Japan (Pathum Thani, Thailand : Asian Institute of Technology, 2022)
Indonesia, as many countries in the world, is struggling with the issues of plastic waste and marine debris, which pose serious threats to the particularly rich marine biodiversity of this region. Knowing about the threat that is haunting the country, Indonesia has tried several efforts in order to solve this issue, including issuing the regulation about the Extended Producer Responsibility (EPR) in Regulation 75/2019 that oblige producers and retailers in Indonesia to take greater responsibility for the management of waste from their products. The EPR requirements in Indonesia actually already exists under the Waste Management Act of 2008 but it{u2019}s not easy to enforce it since the industry is not ready yet to carry out EPR. Therefore, in this research, the challenges that happen in EPR implementation in Indonesia, specifically the plastic recycling industry, was explored by conducting interview to various stakeholders, both the formal and informal sector. The informal sector contributes significantly to the recycling rates in low- and middle income countries, including Indonesia. The formal sector also agreed that it{u2019}s important to formalize the informal sector, but formalizing the informal sector also has its own challenges. 53.5% from 43 respondents of informal sector, which means 23 individuals, are interested to get themselves formalized. By getting themselves formalized, they expect to get more stable income and get better social status/more acknowledged and appreciated by the society. Meanwhile, the other 20 respondents prefer to stay where they are now because they don{u2019}t want to get tied and some feel that there{u2019}s no benefit in doing that. By having a better understanding of the EPR implementation in Indonesia, several recommendations were given for each part of the value chain starting from the upstream, middle-stream, down-stream, and the government. The Upstream should focus more on 2Reduce3 by re-designing their packaging, the Middle-stream should be more educated and start to segregate their waste even without any rewards or incentives, the Down-stream should integrate the informal sector more, and the Government should come up with better implementation and monitoring system for the regulation, do more collaboration with private sector rather than considering them as competitor. This plastic waste issue is a complex issue since it is involving a lot of stakeholders. All the stakeholders should be on the same page to work together to solve this issue, but it all should be started from the regulations by the government. Therefore, unavoidably the government still plays a key role in solving this plastic waste issue.
A research study submitted in partial fulfillment of the requirements for the degree of Master in Marine Plastics Abatement
Research studies project report (M.) - Asian Institute of Technology, 2022
Keywords: Plastic scrap -- Indonesia -- Management; Plastic scrap -- Recycling -- Indonesia